ANALISIS PENGARUH VARIABEL ATMOSFER TOKO, PROMOSI DAN PELAYANAN PRAMUNIAGA TERHADAP IMPULSE BUYING PADA KELAS KONSUMEN BARU DI KOTA SEMARANG - Sri Rahayu Tri Astuti (Faculty of Economics and Business Diponegoro University, 2014)
The purpose of this research is to study about impulse buying at new middle class costumer at Semarang city. The impulse buying is an unplanned purchase of a product. Three independent variables that influenced impulse buying are store atmosphere, promotion and sales person’s service quality. The data processed using multivariate regression with 75 respondents.Keywords : store atmosphere, promotion, sales person’s service quality and impulse buying